ANALISIS DROP TEGANGAN SAAT MANUVER JARINGAN PADA PENYULANG SYG01 DAN SYG09 MENGGUNAKAN SIMULASI SOFTWARE ETAP 12.6.0 - An-Naafi, Rayfaldi Ananda (Universitas Lampung, 2025)
The provision of stable and efficient electricity is highly dependent on quality management in power distribution, one of which is conducting Voltage Drop and Network Maneuver analysis. Voltage drop is a decrease in voltage that occurs when electric current flows in a conductor or electrical component. This is caused by several things, including the internal resistance of the conductor. In the SYG01 feeder, voltage drops often occur due to electrical disturbances, overloads, or cables that are too long. The purpose of this study is to analyze the factors that affect voltage drops in the distribution network as well as network maneuvers and the addition of taps as a solution to reduce the impact of voltage drops when network disturbances occur. By simulating it through ETAP software, it is expected to be able to obtain comparative results before and after network maneuvers with appropriate results.